London IQ : the trivia game for Londoners. (San Francisco : Chronicle Books, 2014)
This one-of-a-kind game offers diehard Londoners the chance to prove their insider status while exploring the city in a whole new way. Multiple-choice questions quiz players' knowledge of London's historic nooks and crannies, hotspots, and favorite pastimes. Correct answers are awarded IQ points, and the team with the highest IQ wins! From the Tower to the Tube, Annabel's to Ye Olde Cheshire Cheese,London IQ promises hours of fun and makes a great gift for any resident or fan of this beloved world capital.
2 of meer spelers - vanaf 14 jaar